2020
DOI: 10.1136/vr.105399
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin wounds in working donkeys in Bukombe, Tanzania

Abstract: BackgroundPreventable wounds are a common welfare issue in working donkeys in many countries. In the Bukombe District of Tanzania, there are estimated to be 3000 working donkeys, used primarily to transport loads for direct income generation. For historical reasons, oxen-yoke carts are used; their design is inappropriate for donkeys and results in serious neck wounds. The project aim was to assess the prevalence and nature of wounds in working donkeys.MethodsIn November 2018, 148 donkeys owned by 48 owners wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
4
12
0
Order By: Relevance
“…Resulting physiological stress can impair immune responses and hinder tissue repair [ 39 ]. These findings are similar to other studies which found that when equids are treated in an aggressive manner, they are more likely to suffer from mistreatment [ 16 ] and poorer welfare standards [ 3 , 12 , 16 , 26 ]. In contrast, handlers that were relaxed with their equids had equids that were at ease, friendly to the approach of the enumerator, had visual contact with other animals and showed no signs of fear.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Resulting physiological stress can impair immune responses and hinder tissue repair [ 39 ]. These findings are similar to other studies which found that when equids are treated in an aggressive manner, they are more likely to suffer from mistreatment [ 16 ] and poorer welfare standards [ 3 , 12 , 16 , 26 ]. In contrast, handlers that were relaxed with their equids had equids that were at ease, friendly to the approach of the enumerator, had visual contact with other animals and showed no signs of fear.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, handlers that were relaxed with their equids had equids that were at ease, friendly to the approach of the enumerator, had visual contact with other animals and showed no signs of fear. These equids were also found to have access to clean water when working and housing of satisfactory size with clean bedding, indicating that the positive attitude of handlers towards their equids was promoting better welfare and more relaxed behaviour in their equids and is in concurrence with other studies [ 3 , 12 , 16 , 26 , 40 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations